Light quality triggers biochemical modulation of Cyanobium sp.—photobiology as tool for biotechnological optimization - Pagels, F. (2020)
Cyanobacteria are able to absorb light over a wide spectral range due to the presence of photoreceptors, making it possible to modulate the production of high-value compounds by inducing specific pathways. In order to evaluate the influence of light quality in cyanobacteria metabolism, Cyanobium sp. was grown in five different light conditions, by using low-pressure sodium vapor lamp (SOX) supplemented with low irradiances of green, red, and blue light and UV radiation compared to a control with only SOX. The effects of light supplementation on biomass productivity, photosynthetic activity, biochemical composition, and total antioxidant capacity were evaluated. No changes in biomass productivity were induced by any light supplements. The supplementation of red light triggered the production of lipids, phycocyanin, carotenoids, and total antioxidant compounds, while supplementation of green light increased the content of carbohydrates and chlorophyll a. Thus, supplementation of blue light and UV radiation showed little or no improvements to the culture, whereas under UV radiation the photosynthetic activity was reduced. Overall, Cyanobium sp. is a promising strain, mainly due to its accessibility to metabolism photoregulation as to produce various bioactive compounds.